The Use Of Listening Team Model To Improving Student’s English Listening Skill At Mts Yusufiah - Febri Wanti; Franscy (Nusantara Journal of Multidisciplinary Science, 2023)
Data analysis techniques are applied using qualitative and quantitative data. Qualitative data was taken from interviews, observation sheets, and documentation. Quantitative data is taken from tests. The results of the analysis show that there has been development in students' abilities in listening skills. This can be seen from the pre-test average of 50.08, the post-test average in the first cycle of 67.91, and the post-test average in the second cycle of 80.94. The percentage of students who scored above 75 in the pre-test was 8 out of 28 students (22.22%), and the percentage of students scoring above 75 in the first cycle was 17 out of 19 students (47.22%). This means an increase of around 47.22%. Then, the percentage of students' scores in the second cycle post-test who scored 75 or more was 32 out of 4 students (80.94%). This means that the increase is about 88.88%. These data show that the use of the listening team model in listening skills is effective, and the data above can be concluded that students' abilities in listening skills have increased by using the listening team model as a learning method. In the qualitative analysis, students also seemed active and enthusiastic in the listening learning process using the listening team model.